Penguatan Karakter Pada Siswa SDN 138 Gegerkalong Girang Melalui Pemahaman Nilai-Nilai Pancasila - Wahyu Wahyu; Feri Hidayat; Sarmita Anatasya; Farah Aziizah; Maulia Depriya Kembara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Pancasila is the foundation for society as well as an ideology to reflect the noble values contained therein. Pancasila as the foundation of life needs to be applied from an early age to build the character of the nation and state. However, at this time many children have not applied Pancasila as a foundation in behavior. The purpose of this study is to determine the level of ability and understanding of grade IV elementary school children about the insight and cultivation of Pancasila values as a foundation in behavior. This research uses Mixed Methods, namely mixed methods, quantitative then qualitative sequential explanatory types to strengthen the main data. The data obtained from this research is based on observation, material provision, questioning, and documentation. The results of research on the understanding of Pancasila in elementary schools have not run optimally because there are obstacles in accepting the learning provided and the character of students who are still not in accordance with the values of Pancasila. In addition, there was a slight increase in knowledge about Pancasila after the material was given.